MAJOR EVENT MANAGEMENT STRATEGIES IN STRENGTHENING TELKOM UNIVERSITY'S REPUTATION (CASE STUDY: TELKOM UNIVERSITY ANNIVERSARY SDGS FOR INDONESIA) - Muhamad Reynaldi Satria Nugraha; Mohamad Syahriar Sugandi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This research analyzes the major event management strategy, specifically of the Telkom University Anniversary "SDGs For Indonesia," to strengthen the institution's image. Using a qualitative case study approach, this research reveals how Telkom University successfully maintained its brand existence and enhanced public image through effective event implementation strategy models. The study also develops a conceptual model of event communication that emphasizes the relationship between innovation, adaptation, and the communication process. Communication plays a vital role, divided into institutional (formal) communication for strategic coordination and technical (interpersonal) communication for rapid problem-solving within the core team. This process extends from pre-event planning, internal communication during the event, to external communication, especially with the media, throughout the event. Good relationships with the media, as demonstrated by Telkom University, maximize reach and build a positive image. Collaboration and adaptability were also key to the event's smooth execution. Evaluation results show a significant positive impact. The event received excellent responses from participants and guests, even attracting interest from other parties to adopt featured products. Media exposure, both conventional and social media, dramatically increased: social media reach rose by 31%, positive sentiment by 11%, and negative news decreased by 40%. This proves that Telkom University's communication and event management strategies successfully strengthened its image and contribution to the SDGs.